Defining and manipulating the epigenetic stability of human embryonic stem cells - Kim, Kee-Pyo (2009)
This thesis aimed to define and manipulate epigenetic stability of human embryonic stem cells (hESCs). The allele-specific expression of 22 imprinted genes was examined in 22 hESC lines by distinguishing parental single nucleotide polymorphisms in genomic DNA and cDNA. Half of the genes examined (PEG10, PEG1, MESTIT1, IGF2, H19, GTL2, NESP55, PHLDA2 and ATP10C) showed variable allele-specific expression between cell lines, indicating vulnerability to disrupted imprinting. However, 8 genes (KCNQ1OT1, NDN, NDNL1, SNRPN, IPW, PEG3, KCNQ1 and CDKN1C) showed consistent monoallelic expression. Moreover, 4 genes (TP73, IGF2R, WT1 and SLC22A18) known to be monoallelically expressed or to exhibit polymorphic imprinting in human tissues were always biallelically expressed. MEST isoform 1, PEG10 and NESP55 showed an association between the variability observed in interline allele-specific expression status and DNA methylation at their imprinting regulatory regions. These evidences demonstrate gene-specific differences in the stability of imprinted loci in hESC lines and identify disrupted DNA methylation as one potential mechanism.